Interaction and Modeling Techniques for Desktop Two Handed Input - Hinckley, Ken; Czerwinski, Mary; Sinclair, Mike (Association for Computing Machinery, Inc., 1998)
We describe input devices and two-handed interaction techniques to support map navigation tasks. We discuss several design variations and user testing of two-handed navigation techniques, including puck and stylus input on a Wacom tablet, as well as a novel design incorporating a touchpad (for the nonperferred hand). To support the latter technique, we introduce a new input device, the TouchMouse, which is a standard mouse augmented with a pair of one-bit touch sensors, one for the palm and one for the index finger. Finally, we propose several enhancements to Buxton's three-state model of graphical input and extend this model to encompass two-handed input transactions as well.